The Evolution of Sharia Accounting Principles in Islamic Civilization: A Historical and Epistemological Review with Contemporary Implications - Faizah Dani Pragita (Journal of Islamic Education and Intellectual Discourse (JIED), 2025)
Islamic accounting is frequently perceived as a modern modification of Western accounting, despite substantial historical evidence that its foundations emerged organically within early Islamic civilization. This study addresses the broader question of how Islamic accounting evolved as both a financial and ethical institution and how it can respond to contemporary global challenges. The purpose of this research is to examine the historical development of Islamic accounting, identify its epistemological challenges in the modern era, and evaluate its potential contribution to ethical finance and sustainability. Using a qualitative design, the study employs historical analysis, hermeneutic interpretation, and discourse analysis. Data consist of classical Islamic administrative records, fiqh texts, hisbah manuals, modern standards such as AAOIFI and PSAK Syariah, and contemporary scholarly articles. Data collection followed purposive sampling of relevant documents, while analysis involved thematic coding and cross-textual comparison. Results show that accounting practices were institutionalized as early as the Prophet Muhammad’s era, strengthened under the Khulafā’ al-Rāshidīn—especially through the Bayt al-Māl—and formalized during the Abbasid period through market regulation and ethical oversight. Contemporary findings reveal that Islamic accounting still relies heavily on Western frameworks, faces challenges from digital finance, and struggles to embed Islamic ethical objectives fully. The implications suggest that Islamic accounting can support global agendas such as ESG and sustainable development by operationalizing maqasid al-shariah in reporting systems. In conclusion, the study highlights the need for epistemological reconstruction, digital Sharia governance, and deeper sustainability integration, offering clear directions for future research and policy development. Akuntansi syariah sering dianggap sebagai modifikasi modern dari akuntansi Barat, meskipun terdapat bukti sejarah yang kuat bahwa fondasinya muncul secara organik dalam peradaban Islam awal. Penelitian ini menjawab pertanyaan yang lebih luas tentang bagaimana akuntansi syariah berevolusi baik sebagai institusi keuangan maupun etika dan bagaimana akuntansi syariah dapat menjawab tantangan global kontemporer. Tujuan dari penelitian ini adalah untuk mengkaji perkembangan historis akuntansi syariah, mengidentifikasi tantangan epistemologisnya di era modern, dan mengevaluasi potensi kontribusinya terhadap keuangan dan keberlanjutan yang beretika. Dengan menggunakan desain kualitatif, penelitian ini menggunakan analisis historis, interpretasi hermeneutik, dan analisis wacana. Data terdiri dari catatan administrasi Islam klasik, teks fikih, manual hisbah, standar modern seperti AAOIFI dan PSAK Syariah, dan artikel ilmiah kontemporer. Pengumpulan data dilakukan dengan cara purposive sampling terhadap dokumen-dokumen yang relevan, sementara analisis dilakukan dengan cara pengkodean tematik dan perbandingan lintas teks. Hasil penelitian menunjukkan bahwa praktik akuntansi telah dilembagakan sejak era Nabi Muhammad, diperkuat di bawah Khulafā' al-Rāsyidīn-terutama melalui Baitul Mal-dan diformalkan pada masa Abbasiyah melalui regulasi pasar dan pengawasan etika. Temuan kontemporer mengungkapkan bahwa akuntansi syariah masih sangat bergantung pada kerangka kerja Barat, menghadapi tantangan dari keuangan digital, dan berjuang untuk menanamkan tujuan etika Islam sepenuhnya. Implikasinya menunjukkan bahwa akuntansi syariah dapat mendukung agenda global seperti ESG dan pembangunan berkelanjutan dengan mengoperasionalkan maqasid al-syariah dalam sistem pelaporan. Sebagai kesimpulan, penelitian ini menyoroti perlunya rekonstruksi epistemologis, tata kelola Syariah digital, dan integrasi keberlanjutan yang lebih dalam, yang menawarkan arahan yang jelas untuk penelitian dan pengembangan kebijakan di masa depan.